Prognostic Value of Coronary Angiography-Derived Fractional Flow Reserve Immediately After Stenting - Zhou, Zuoyi; Zhu, Baozhen; Fan, Fangfang; Yang, Fan; Fang, Shu; Wang, Zhi; Qiu, Lin; Gong, Yanjun; Huo, Yong (Frontiers in Cardiovascular Medicine, 2022)
Objectives The aim of this study was to investigate the potential prognostic value of post-percutaneous coronary intervention (PCI) angiography-derived fractional flow reserve (FFR) and its gradient across stent. Background Post-PCI FFR and its gradient across stent have been proved to be associated with clinical outcomes. However, little was known about the prognostic value of post-PCI coronary angiography-derived FFR and its gradient across stent. Methods Patients diagnosed with coronary heart disease and participated in drug-eluting stent (DES) clinical trials for stent implantation in a single center were included for this retrospective analysis. A novel coronary angiography-derived FFR (caFFR) and its gradient across stent were calculated offline using two projections from coronary angiography performed after PCI. Clinical follow-up was completed at 9 months after the index procedure, the primary outcome was target vessel failure (TVF), defined as a composite of target vessel-related myocardial infarction (MI), target vessel-related revascularization (TVR) and cardiac death. A coronary angiography was also performed at the 9 months follow-up time to get data of late lumen loss (LLL) and percent diameter stenosis (%DS). Results A total of 159 vessels in 136 patients were analyzed. The mean value of post-PCI caFFR was 0.90 ± 0.06. The median value of trans-stent caFFR gradient (△caFFRstent) was 0.04 (interquartile range 0.02-0.08). △caFFRstent>0 was demonstrated in 147 vessels (92.45%). TVF rate was significantly higher in patients with post-PCI caFFR<0.90 (4 [8.16%] vs 1 [1.15%], P=0.037), which was mainly achieved by the difference between TVR rate. In the subgroup with lesions located in left anterior descending coronary artery (LAD) post-PCI caFFR was an independent predictor of LLL (β=-1.07, 95% CI:-1.74 to -0.39, P=0.002) and %DS at follow-up (β=-30.24, 95% CI:-56.44 to -4.04, P=0.025), △caFFRstent was an independent predictor of LLL (β=0.98, 95% CI:0.13-1.83, P=0.026). Conclusion Suboptimal post-PCI caFFR and trans-stent caFFR gradient were common among vessels immediately after stenting. Lower post-PCI caFFR was associated with higher rate of 9-month TVF. After LAD PCI, both post-PCI caFFR and its gradient across stent were independent predictors of neointimal proliferation of the target vessel evaluated by LLL and %DS at follow-up.